EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT AMONG MANAGEMENT AND SCIENCE UNIVERSITY’S (MSU) SCHOOL OF EDUCATION AND SOCIAL SCIENCES (SESS) STUDENTS - Afandi, Nur Sabrina; Abu Bakar, Abu Yazid (Bisma The Journal of Counseling, 2019)
This study aims to look at the existing level of emotional intelligence among Management and Science University?s (MSU) School of Education and Social Sciences (SESS) students. It will also look at the relationship between intrapersonal and interpersonal level among SESS students. The sample is 100 students that divide by 50 males and 50 females. In this research, it used a survey tool which Emotional Competencies Inventories (ECI). In this research it used inventory with 40 items in it. It is divided to two parts, intrapersonal and interpersonal abilities. First is to recognize emotions categories of self. Second is emotional self-management and lastly personal motivation.  Interpersonal part is consists of two categories, which is the ability to recognize others feelings and the ability to handle relationships effectively. This researcher analyzes the data using the Statistical Package for the Social Science (SPSS) version 17.0. The reliability for this instrument (Emotional Intelligent Inventory) is .791. The data was process by using the descriptive statistics of the mean score and the standard deviation. Pearson correlation coefficient is used to measure the relationship between the construct of intrapersonal and interpersonal relationships among the students. The results showed that each of the questions and objectives of the study have been answered. The results of the study also illustrate the level of emotional intelligence among SESS students are at moderate level. This study also discusses the results of the study, future research recommendations and limitations of the study